Production of mangifera indica powder using spray dryer and the effects of drying on its physical properties - Siti Nadirah, Md Zaini (2009)
The objective of this work was to study the influence of spray drying conditions on the physical properties of mango powder. The process was carried out on a mini spray dryer and maltodextrin 10DE was used as carrier agent. Three tests were made. Solubility, dissolution and moisture content were analyzed as responses. Solubility was positively affected by inlet air temperature while dissolution and moisture content of powders were negatively affected by inlet air temperature. An increase in maltodextrin concentration increases the solubility of the mango powders and decreases the dissolution of the powders. From the result obtain the inlet air temperature of 160oC and 15% of maltodextrin addition is the optimum value for this study. For the solubility test, the optimum value is at temperature of 170oC and 20% of maltodextrin addition which the percentage of solubility is 81.76. The inlet air temperature of 150oC and maltodextrin addition of 10% is the optimum value for the dissolution test. For moisture content analysis, the optimum value is at inlet air temperature of 160oC and 15% maltodextrin addition which the percentage of moisture content is 2.38.